Hydrothermal conversion of xylose, glucose, and cellulose under the catalysis of transition metal sulfates. (15th March 2015) - Cao, Xuefei; Peng, Xinwen; Sun, Shaoni; Zhong, Linxin; Chen, Wei; Wang, Sha; Sun, Run-Cang
Highlights: Zn 2+ and Ni 2+ showed obvious effect on converting biomass into lactic acid. Cu 2+ and Fe 3+ could accelerate the formations of levulinic acid and formic acid. Positive correlations among xylose, glucose, and cellulose degradation were observed. HTC of monosaccharide can be used to screen catalysts for biomass upgradation. Abstract: Hydrothermal conversion (HTC) is an important thermochemical process to upgrade low-cost biomass into valuable chemicals or fuels. As compared with non-catalytic HTC, catalytic HTC shows high energy efficiency on biomass upgradation. In this work, the catalytic performances of various transition metal sulfates (Mn 2+, Fe 2+, Fe 3+, Co 2+, Ni 2+, Cu 2+, and Zn 2+ ) in the HTCs of xylose, glucose, and cellulose under different conditions were explored. Among these catalysts, Zn 2+ and Ni 2+ showed obvious effects on the conversions of xylose, glucose, and cellulose into lactic acid, while Cu 2+ and Fe 3+, which could significantly accelerate the hydrolysis of cellulose into glucose at 200 °C, displayed high efficiency on converting glucose and cellulose into levulinic acid and formic acid at high temperature. Additionally, significant positive correlative relationships among xylose, glucose, and cellulose degradations were observed. This study is helpful for screening appropriate catalysts for biomass upgradation through catalytic HTC of monosaccharide.